Shariah Disclosure in Islamic Banking: Comparison of Islamic Banks in Indonesia and Malaysia - Nisa Rahma Fadila; Rifqi Muhammad; Titin Subekti; Peni Nugraheni; Nor Farizal Mohammed (Economica: Jurnal Ekonomi Islam, 2021)
The development of Islamic banking, especially in Indonesia and Malaysia, has made the two developing countries experience an increase in assets and financing disbursed. This fact provides good news regarding the growth of the Islamic banking sector in both countries, as well as challenges in implementing good governance to maintain compliance with sharia principles. This study aims to measure the level of Sharia disclosure with seven indicators developed from previous research. The objects in this study are Islamic banks in Indonesia and Malaysia in the 2016-2018 period. The results show that Islamic banks in both countries have not met the perfect aspects of Sharia disclosure by getting an index of less than 1, namely 0.76 for Islamic banks in Indonesia, and 0.57 for Islamic banks in Malaysia. The results of this study are expected to be a means of improvement for the management of Islamic banks in both countries to be more comprehensive in the disclosure of Sharia in the annual report. The novelty of this research is the combination of sharia disclosure indicators from previous studies.